Granulocyte macrophage colony-stimulating factor enhances the modulatory effect of cytokines on monocyte-derived multinucleated giant cell formation and fungicidal activity against Paracoccidioides brasiliensis - Nascimento, Magda Paula Pereira do [UNESP]; Bannwart, Camila Ferreira [UNESP]; Nakaira-Takahagi, Erika [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2011)
Multinucleated giant cells (MGC) are cells present in characteristic granulomatous inflammation induced by intracellular infectious agents or foreign materials. The present study evaluated the modulatory effect of granulocyte macrophage colony-stimulating factor (GM-CSF) in association with other cytokines such as interferon-gamma (IFN-γ), tumour necrosis factor-alpha, interleukin (IL)-10 or transforming growth factor beta (TGF-β1) on the formation of MGC from human peripheral blood monocytes stimulated with Paracoccidioides brasiliensis antigen (PbAg). The generation of MGC was determined by fusion index (FI) and the fungicidal activity of these cells was evaluated after 4 h of MGC co-cultured with viable yeast cells of P. brasiliensis strain 18 (Pb18). The results showed that monocytes incubated with PbAg and GM-CSF plus IFN-γ had a significantly higher FI than in all the other cultures, while the addition of IL-10 or TGF-β1 had a suppressive effect on MGC generation. Monocytes incubated with both pro and anti-inflammatory cytokines had a higher induction of foreign body-type MGC rather than Langhans-type MGC. MGC stimulated with PbAg and GM-CSF in association with the other cytokines had increased fungicidal activity and the presence of GM-CSF also partially inhibited the suppressive effects of IL-10 and TGF-β1. Together, these results suggest that GM-CSF is a positive modulator of PbAg-stimulated MGC generation and on the fungicidal activity against Pb18.
Keywords: Paracoccidioides brasiliensis; cytokines; multinucleated giant cells; fungicidal activity